Anonim şirketlerde borsaya kote olmayan nama yazılı paylar üzerinde kaçınma klozunun kullanılması - İncesu, Elif Bilge (İstanbul Bilgi Üniversitesi, 2022)
ÖZET: 6102 sayılı Türk Ticaret Kanunu’nun benimsediği temel ilke nama yazılı payların herhangi bir sınırlamaya tabi olmaksızın serbestçe devredilebilmesidir. Payın serbestçe devredilebilirliği ilkesi mutlak değildir ve payların devri, iradi (esas sözleşmesel) veya kanuni olarak sınırlandırılabilir. TK md. 493 uyarınca anonim şirketler, geçerli bir esas sözleşmesel bağlam rejiminin varlığı halinde, payları borsada işlem görmeyen bağlı nama yazılı payların devrinde, devre konu payları kendi adına ve kendi, diğer pay sahipleri veya üçüncü kişiler hesabına gerçek değeri üzerinden satın almayı teklif ederek herhangi bir gerekçe göstermeksizin devre onay vermekten kaçınabilir. Anonim ortaklıklara kanunen tanınan bu imkân kaçınma klozu (escape clause) olarak adlandırılmaktadır. Kaçınma klozu anonim şirketlere, pay sahiplerinin çevresinin bileşiminin korunması bakımından şirket dışında tutmak istedikleri kişilere yapılan pay devirlerini engelleme fırsatı vermektedir. Çalışmamızda temel olarak, TK düzenlemeleri uyarınca; kaçınma klozunun hukuki niteliği, kullanım koşulları, şirket tarafından yapılacak alım teklifi, gerçek değerin tespiti ve kaçınma klozunun kullanılması halinde hakların taraflara geçişi konuları bu bağlamda ortaya çıkabilecek soru ve sorunlarla birlikte ele alınmıştır.

ABSTRACT: Registered shares shall be freely transferred without any restriction as per the main principle adopted by the Turkish Commercial Code numbered 6102. Given the main principle of free transfer of registered shares, such principle is not absolute, and the transfer of registered shares may be restricted by will of the shareholders (under articles of association) or by statutory obligations. As per the Article 493 of the Turkish Commercial Code, joint stock companies are entitled to reject the transfer of non-listed registered shares and offer to purchase the shares to be transferred on their own behalf, other shareholders or third parties at the going concern value of the relevant shares, without giving any reason in the case of a valid share transfer restrictions regime under the articles of association. This opportunity provided to joint-stock companies is referred as the escape clause. Escape clause gives joint stock companies the opportunity to prevent share transfers to third parties which the Company wishes to exclude from the shareholders in order to protect the composition of its shareholders structure. In our thesis, mainly, the legal nature of the escape clause, the terms of its use, the purchase offer to be made by the Company, the determination of the going concern value and the transfer of rights to the parties are reviewed under the relevant articles of Turkish Commercial Code together with the questions and problems that may arise in this context.
The use of escape clause on non-listed registered shares in joint stock companies
Keywords: Pay Devri; Bağlam; Kaçınma Klozu; Anonim Şirketler; Alım Teklifi; Share Transfer; Share Restrictions; Escape Clause; Joint Stock Companies; Purchase Offer